An Analysis of Novice Teacher’s Questioning Types During the Microteaching Classroom - Selvi Yuliani; Indriani, Lilia (Universitas PGRI Adi Buana Surabaya, 2021)
The only thing that is expected in classroom learning activities is the achievement of learning objectives. One of the efforts to achieve the learning objectives is to always communicate with students, such as asking questions. This study aims to determine the query used by novice teachers during their micro-teaching practice in teaching Senior High School students. The theory of Lockhart (1994) is used in this research. Researchers used qualitative methods in processing data. The data obtained from the results of classroom observations with video zoom recording and documentation. The data sources for this study were taken from 10 novice teachers at one of the universities in Indonesia. The author took the data to find out what the novice teacher used during they were doing micro teaching classroom. As a result, the types of question that the teacher used are procedural question, convergent question, and divergent question. Then, the type of question that frequently uses is convergent question. The questions that novice teachers in teaching often use do not require high thinking.